Obesity Interventions in Underserved Communities : Evidence and Directions - Zambrana, Ruth E.; Kumanyika, Shiriki Kinika, 1945-; Brennan, Virginia M. (Book collections on Project MUSE., 2014)
The obesity epidemic has a disproportionate impact on communities that are hard-hit by social and economic disadvantages. In Obesity Interventions in Underserved Communities, a diverse group of researchers explores effective models for treating and preventing obesity in such communities.